Os recursos das redes sociais e suas potencialidades para a aprendizagem - Cabral, Mayara Kaynne Fragoso (Universidade Federal do Tocantins, 2018)
The Social Networks (SN) are a phenomenon between different student profiles. To study the potential use of social networks as a educational environments, provides an opportunity to analyze their different characteristics that may facilitate the process of designing learning strategies. This research has as general objective, to identify resources in social networks, with potential for learning and the integration of these networks on Virtual Learning Environments (VLE), and as the specific objectives: identify the availability of social networks in the virtual environments of learning: analyze the availability of popular Social Networking Sites (SNS) resources, that can be used in the school environment, teaching resources as promoters of learning; up, based on literature, indicators of how research used the social network Facebook in the construction process of learning. The results showed that 54% of software used as VLE by 110 surveyed educational institutions, allow integration with social networks, whether external or internal, however, the majority of educational institutions still opt for not integrating to the SNS because institutional constraints, lack demand or interest. Analyses made on Facebook, Google+ and Twitter, show that Facebook and Google+ have five of the teaching resources considered important for learning, not having only the teacher assessment feature. In the case of Facebook, the review of 26 studies showed that 71% of researchers use questionnaires built in other tools to conduct assessments or investigations on the network, and that 50% use similar groups to a learning environment.